The Effectiveness of Training Emotional Regulation Skills in Reducing Addiction Ability in Male High School Students - Ramin Habibi-Kaleybar; Safarali Dehghani (Gonabad University of Medical Sciences, 2021)
Background: Emotional adjustment skills have recently been proposed as a new framework in the prevention of addiction in students. The purpose of this study was to determine the effectiveness of training emotional regulation skills on reducing addiction ability in high school male students. Methods: The statistical population of the present quasi-experimental study with a pre-test, post-test design and a control group was male high school students in Tabriz District 3 in the academic year 2018-2019. Accordingly, using the cluster sampling method, the students of one school were selected as the statistical sample and those with higher than the average score (above 21) were selected randomly and divided into the experimental (n=25) and control (n=25) groups. The experimental group was subjected to Emotional regulation skills training for 8 sessions, each session lasting 90 minutes for two months. During this period, the control group received no intervention. Theoretical Addiction Questionnaire was used for data collection. Covariance analysis was used to analyze the results.  Results: Data analysis showed that training of emotional regulation skills has an impact on reducing the addiction of talented students.  Conclusion: Training emotional regulation skills has an impact on reducing the addiction of talented students. emotion regulation skills training can also be used as a coping approach in adolescent education that should be targeted by reference groups, such as counselors, school coaches, and social planners.